2013
DOI: 10.1371/journal.pone.0073447
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cell Count Measured Prior to Cancer Development Is Associated with Future Risk of Venous Thromboembolism – The Tromsø Study

Abstract: BackgroundElevated white blood cell (WBC) count is associated with risk of venous thromboembolism (VTE) in cancer patients initiating chemotherapy. It is not known whether the risk of VTE by WBC count in cancer patients is causal or merely a consequence of the malignant disease. To address this question, we studied the association between WBC count, measured prior to cancer development, and risk of VTE in subjects who did and did not develop cancer during follow-up in a prospective population-based study.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 36 publications
0
27
2
1
Order By: Relevance
“…Our data suggest that higher WBC peak at mobilization and stem cell engraftment could increase the risk for thrombosis, although we lacked statistical significance. The connection between leukocytosis, particularly neutrophilia, and thrombosis in cancer patients is under active investigation 19, 20 21, 22 For example Khorana risk score for VTE in cancer patients was developed to predict the risk for cancer patients depending of type of cancer. 23 Using the predictive model, diagnosis of Hodgkin’s lymphoma, elevated prechemotherapy platelet count, and leukocyte count above 11 × 10/L each independently increase VTE risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that higher WBC peak at mobilization and stem cell engraftment could increase the risk for thrombosis, although we lacked statistical significance. The connection between leukocytosis, particularly neutrophilia, and thrombosis in cancer patients is under active investigation 19, 20 21, 22 For example Khorana risk score for VTE in cancer patients was developed to predict the risk for cancer patients depending of type of cancer. 23 Using the predictive model, diagnosis of Hodgkin’s lymphoma, elevated prechemotherapy platelet count, and leukocyte count above 11 × 10/L each independently increase VTE risk.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a study by Blix et al . in Tromsø found that cancer patients with a high pre‐cancer leukocyte count (≥ 8.6 × 10 9 cells L −1 ) (20% of the patients) had a 2.4‐fold higher risk of VTE than those with a lower leukocyte count (< 6.4 × 10 9 cells L −1 ). Leukocytosis is also related to poor prognosis in cancer patients .…”
Section: Role Of Leukocytes In Vte In Cancer Patientsmentioning
confidence: 99%
“…Consistent with this hypothesis, an approximately twofold higher risk of VTE was demonstrated in patients with elevated NLR, which is in agreement with the experimental demonstration that neutropenia confers protection against DVT amplification in an in vivo model 17 and with the clinical observation that white blood cell and neutrophil counts measured prior to cancer development are associated with future VTE risk in a prospective populationbased study. 18 An appealing hypothesis recently drawn to explain the causal relationship between neutrophils and cancer-associated VTE was founded on the capability of cancer microenvironment to predispose neutrophils to release neutrophil extracellular traps (NETs). 19 NET formation, indeed, has been implicated in lung thrombosis in a breast carcinoma model 20 and in thrombus organization in human VTE.…”
Section: Short Reportmentioning
confidence: 99%